The Price Is Wrong! - (:unkn) unknown (My University, 2013)
This presentation, which compares the cost of journal subscriptions to items such as Corvettes and diamond rings, ran on a loop in the University of Wisconsin, Milwaukee library in the days leading up to an Open Access Day event.